EGMR 11329/85 vom 18. Dezember 1987 , CASE OF F. v. SWITZERLAND - Hudoc Ch (1987)
Violation of Art. 12;Non-pecuniary damage - finding of violation sufficient;Costs and expenses award - domestic proceedings;Costs and expenses award - Convention proceedings; Violation: 12